Interest as a Structural Component of Individual Legal Consciousness - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2022)
The article substantiates a position that has not received the support of most scientists: along with feelings, emotions, experiences and other elements of the legal psychology of individual legal consciousness, which reflect the attitude to law, interest is one of the constituent components. The author emphasizes the necessity and prospects of studying legal psychology and its elements, since they are not always of secondary importance in relation to legal ideology.